PENGARUH POLITICAL ISSUE, SOCIAL IMAGERY, CANDIDATE PERSONALITY, SITUATIONAL CONTIGENCY DAN EPISTEMIC VALUE TERHADAP PERILAKU KEPUTUSAN PEMILIH KOTA PEKANBARU” STUDI PADA PEMILIHAN GUBERNUR PROVINSI RIAU 2018” - Muhammad Ilham Oloan; Veri nita (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This research was conducted to find out the influence of Political Issue, Social Imagery, Candidate Personality, Situational Contingency, Epistemic Value on the behavior of voter decisions in Pekanbaru in the election of the Governor of Riau 2018. To determine the sample in this study using purposive sampling criteria: (a) Including DPT in the city of Pekanbaru (b) Following the Election of the Governor of Riau 2018. This study used a sample size of 180 respondents obtained from the Hair method. This research uses quantitative descriptive method with multiple linear regression analysis assisted by SPSS 25 software. The results of this study reveal that political issue, social imagery and epistemic value influence the Voters' Choice Behavior, while candidate personality and situational contingency do not affect the Voters' Choice Behavior in Pekanbaru. From the R2 value obtained of 51.5%. This means that all independent variables explain 51.5% of the dependent variable. While the rest is influenced by other variables not examined in this study.